Rehabilitation of postural stability in ataxic/hemiplegic patients after stroke - Januário, F (2010)
Purpose. This study assesses the postural stability and the effect of balance training using a force platform visual biofeedback among outpatients with postural disturbances following stroke. Method. A tilting multiaxial force platform was used to assess bilateral postural stability in 38 outpatients (mean age 69.50 +/- 8.57 years) with hemiplegia and/or ataxia after stroke. Stability indexes were obtained. Afterwards, a subgroup of 12 patients with the poorest overall stability index (OASI) started a balance training programme in the force platform. Postural control training consisted of a 30-min training session once a week for a 15-week period. The test was then repeated. Results. In the 38 outpatients sample, the mean OASI was 4.7 +/- 2.0 and 42.1% of the patients used their hands for support. In the 12 outpatients group, the initial OASI was 5.8 +/- 2.3 and half of the patients used their hands for support. The final OASI was 3.3 +/- 1.0 (p = 0.005) and only two of the patients used their hands for support (p = 0.046). Conclusion. Our results suggest that a training programme using force platform visual biofeedback improves objective measures of bilateral postural stability in patients with hemiplegia and/or ataxia after stroke.